If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -3) + 8(x + 6) = 4(8 + -7x) Reorder the terms: 9(-3 + x) + 8(x + 6) = 4(8 + -7x) (-3 * 9 + x * 9) + 8(x + 6) = 4(8 + -7x) (-27 + 9x) + 8(x + 6) = 4(8 + -7x) Reorder the terms: -27 + 9x + 8(6 + x) = 4(8 + -7x) -27 + 9x + (6 * 8 + x * 8) = 4(8 + -7x) -27 + 9x + (48 + 8x) = 4(8 + -7x) Reorder the terms: -27 + 48 + 9x + 8x = 4(8 + -7x) Combine like terms: -27 + 48 = 21 21 + 9x + 8x = 4(8 + -7x) Combine like terms: 9x + 8x = 17x 21 + 17x = 4(8 + -7x) 21 + 17x = (8 * 4 + -7x * 4) 21 + 17x = (32 + -28x) Solving 21 + 17x = 32 + -28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28x' to each side of the equation. 21 + 17x + 28x = 32 + -28x + 28x Combine like terms: 17x + 28x = 45x 21 + 45x = 32 + -28x + 28x Combine like terms: -28x + 28x = 0 21 + 45x = 32 + 0 21 + 45x = 32 Add '-21' to each side of the equation. 21 + -21 + 45x = 32 + -21 Combine like terms: 21 + -21 = 0 0 + 45x = 32 + -21 45x = 32 + -21 Combine like terms: 32 + -21 = 11 45x = 11 Divide each side by '45'. x = 0.2444444444 Simplifying x = 0.2444444444
| 0.1(x+100)+0.1x=1 | | -1*[-2]=x | | -36-2x+9x=3x+12 | | 5(t-2)-3t=4(2+4)-9 | | 4(2x+9)=20 | | 8a^2+4a= | | 9+n=2n-4 | | 9-10x=94-45x | | (x+2)(2x-3)=0 | | 4x-11x+7=4 | | 5(x+2)+x=3(x-1)+1 | | 24+0.99x=1.49x | | 4(v-3)-6v=-2(v+6) | | 15=-8(c-1)+9 | | x^6-9x^3+20=0 | | 4(v-3)-6v=2(v+6) | | 5(2+y)-y=10+4(y+1) | | 8(2x+3)=56 | | 4x^3+22x^2+52x=0 | | 7(2k-1)+4=7 | | -2(w+4)+6w=4(w-3) | | -x+3=9 | | 5(2x+3)=45 | | -4(v+3)-3v=2(v+3) | | -2(x+4)+6w=4(w-6) | | 12-C+15-C=7 | | 5ax+bx=5abx | | 4(3+x)-x=6+3(x+2) | | 5ax+bx=#5ab2x | | y=56-2 | | 21=9-2(4a+2) | | 3x+8=33 |